Modulation of surface states by phosphorus to improve the optical properties of ultra-small Si nanocrystals. (31st October 2017) - Li, Dongke; Jiang, Yicheng; Liu, Jingjing; Zhang, Pei; Xu, Jun; Li, Wei; Chen, Kunji
Abstract: Here, we report the enhanced luminescence and optical gain by appropriate P-doping in Si nanocrystals (NCs)/SiO2 multilayers with ultra-small size of ∼1.9 nm. The luminescence intensity is enhanced by 19.4% compared to that of an un-doped NC and the optical gain is as high as 171.8 cm −1, which can be attributed to the reduction of surface defect states by the passivation of P impurities as revealed by electron spin resonance spectra. Further increasing the P-doping ratios results in the increase of conduction electrons due to the substitutional doping of phosphorus in the Si NCs, which favors the Auger recombination process. Consequently, both the luminescence intensity and the optical gain decrease rapidly. It is demonstrated that introduction of the suitable impurities can effectively modulate the surface chemical environment of Si NCs, which provides a new way to control the physical properties of Si NCs.